Political determinants and impact analysis of using a cable system as a complement to an urban transport system - Escobar, Diego; Garcia, Francisco; Cadena-Gaitan, Carlos (2013)
The construction of cable propelled systems fully integrated to urban public transport systems has become an innovative trend in recent years, for some Colombian cities.The most prominent examples include the cities of Medellin and Manizales, where these infrastructures have been built and have been running for several years.In fact, it should be highlighted that Manizales hosted, during the first half of the 20th century, the longest cable system in the world, which operated for nearly forty years and was a cornerstone in the development of the region.This historic cable allowed for the transportation of large shipments of coffee to the Magdalena River, so that they could be exported all over the world.In this paper we provide a thorough assessment of the cable system in Manizales. We evaluate its costs, in a comparative perspective against the impacts generated by the system, via time savings in daily travel; due to its full integration with the public transport system, we also provide empirical evidence or the related passenger demand variability.Upon the implementation of the first cable system, additional similar projects have been initiated.We provide an insight into a cable system designed for recreation, currently being built, and describe the planning process for the most recent public transport cable system being designed.All these systems are evaluated from the supply-side, measuring accessibility, from the demand-side, modeling the complete urban transport system for the city, and from the political side, describing the determinants of the decisions that ultimately stimulate the implementation of these projects in sustainable mobility.Based on the results obtained, we offer conclusions in regards to the actual competitiveness of cable propelled systems, arguing on whether these should be considered as valid urban passenger transport solutions.